Al-Tadhâd Al-Ma’nawi fî Surati Al-Mâidati - Ahmed, Nazifi Sheik; Mukit, Mukit; Haruna, Haruna Abubakar (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2023)
Purpose- This research aims to explore the study of contradictions (tadlād) in meaning found in Surah Al-Maidah. Tadlād is a study in the realm of semantic beauty known as thibāq in the science of Badi'. This study presents an interesting discussion regarding the aesthetic appeal of a sentence when viewed in terms of the selection of its words. Design/ Methodology/ Approach- The research method employed is qualitative, specifically library research and content analysis of Surah Al-Maidah using the tadlād maknawy theory in thibaq studiy. Findings- The research findings indicate that there are 22 instances of thibāq in Surah Al-Maidah, with a breakdown of 15 instances of thibāq ijab, 6 instances of thibāq salab, and 1 instance classified as thibāq khafi or iham al-tadlād. The study also highlights the important distinction between al-tadlād and al-muqābalah, which is often misunderstood. Research Limitation/ Implication- The impact of this research is to strengthen the faith of Muslims in experiencing the beauty of the Qur'an, particularly in Surah Al-Maidah. Additionally, there are several important findings, such as the distinction between muqābalah and tadlād, which are often mistakenly understood as the same thing. This research contributes significantly to the study of thibāq and provides valuable insights for further exploration.